Myocardial Performance Improvement After Iron Replacement in Heart Failure Patients - Ramos-Polo, Raúl (2025)
Background: Iron deficiency (ID) is a commonly seen comorbidity in heart failure (HF) patients. It is often associated with a poor prognosis and impaired physical capacity. The functional limitations linked to ID may lead to cardiac function abnormalities. The functional limitations linked to ID may lead to cardiac function abnormalities, that can be reversible after iron repletion. Some echocardiographic parameters, such as global longitudinal strain (GLS), myocardial work (MW) and its derivatives constructive work (CW), wasted work (WW) and work efficiency (WE), may be of added value in advanced cardiac performance assessment. Methods: IRON-PATH II was a multicenter, prospective and observational study designed to describe the pathophysiological pathways associated with ID. The echo-substudy included 100 HF patients that had undergone a specific pilot echocardiographic evaluation. Patients had a left ventricular ejection fraction (LVEF) ≤50%, were in stable clinical condition and on standard HF medication with hemoglobin ≥11 g/dL. The final cohort included 98 patients. Results: The ID group showed worse cardiac function, with lower GLS (−8.5 ± 9% vs. −10 ± 10%), WE (74 ± 10% vs. 80 ± 10%) and MW (665 [453–1013] vs. 947 [542–1199] mmHg%), as well as higher WW (290 [228–384] vs. 212 [138–305] mmHg%) and lower RV free wall strain (−13 [−20–(−11)]% vs. −17 [−23–(−14)]%). Following iron repletion, ID patients demonstrated improved LV (GLS, MW, WE and WW) and RV performance (RV free wall strain), aligning with non-ID patients (all p-values >0.05 compared to the non-ID group). Conclusions: Among HF patients with reduced LVEF, ID was associated with worse myocardial performance in both the LV and RV. All the alterations seen were reversible after intravenous iron repletion.